Relationship between iron intake and iron status to stunted in children aged 24-35 months during the COVID-19 pandemic in Jakarta - Akbar Husaini Angkat; Dian Novita Chandra; Novi Silvia Hardiany (Indonesian Nutrition Association, 2022)
Covid 19 pandemic has caused changes in the socioeconomic conditions, affects parents' ability to sustain their children nutritious food. If nutrients are insufficient for a long term is causing growth to be stunted.